Improving the quality of mathematics teacher education: An integrated approach to the 4C skills - Dahlan, Taufiqulloh; Judijanto, Loso; Hali, Fitriyani (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2024)
With the development of increasingly sophisticated technology, educators must have an appropriate learning model in teaching. On the other hand, a country's obligation is to provide facilities and support teachers in developing their competencies. Currently in Indonesia, there is minimal use of 4C skills teaching. Forms of support should be given to teachers to apply 4C to students in schools. However, the fact is, learning 4C skills is very difficult. Therefore, the purpose of this study is to analyze the obstacles and difficulties in teaching 4C skills. The research method used is qualitative and the data collection method is by interviewing 24 respondents. The data analysis technique is with comparative analysis. The results of the study identified five obstacles, namely lack of competency and motivation support, initial knowledge of 4C, minimal references and political mixtures into the curriculum. Pedagogical competence is also problematic. Conclusion, moral and material support is needed for teachers in preparing, designing materials, implementing, assessing and evaluating 4C learning and schools and the government need to think about the form of routine training for teachers in schools in teaching 4C skills. This study recommends that 4C skills be specifically focused on the education curriculum in Indonesia.